Clinical experience of scoring criteria for Familial Hypercholesterolaemia (FH) genetic testing in Wales. Issue 1 (May 2015) - Haralambos, K.; Whatley, S.D.; Edwards, R.; Gingell, R.; Townsend, D.; Ashfield-Watt, P.; Lansberg, P.; Datta, D.B.N.; McDowell, I.F.W.
Abstract Background/Objective Familial Hypercholesterolaemia (FH) is caused by mutations in genes of the Low Density Lipoprotein (LDL) receptor pathway. A definitive diagnosis of FH can be made by the demonstration of a pathogenic mutation. The Wales FH service has developed scoring criteria to guide selection of patients for DNA testing, for those referred to clinics with hypercholesterolaemia. The criteria are based on a modification of the Dutch Lipid Clinic scoring criteria and utilise a combination of lipid values, physical signs, personal and family history of premature cardiovascular disease. They are intended to provide clinical guidance and enable resources to be targeted in a cost effective manner. Methods 623 patients who presented to lipid clinics across Wales had DNA testing following application of these criteria. Results The proportion of patients with a pathogenic mutation ranged from 4% in those scoring 5 or less up to 85% in those scoring 15 or more. LDL-cholesterol was the strongest discriminatory factor. Scores gained from physical signs, family history, coronary heart disease, and triglycerides also showed a gradient in mutation pick-up rate according to the score. Conclusion These criteria provide a useful tool to guide selection of patients for DNA testing when applied by health professionals who have clinical experience of FH.